Rapid defense mechanism suppression during viral- oomycete disease complex formation - Philosoph, Amit M.; Dombrovsky, Aviv; Luria, Neta; Sela, Noa; Elad, Yigal; Frenkel, Omer (Frontiers in Plant Science, 2023)
Combined infection of the host plant with pathogens involving different parasitic lifestyles may result in synergistic effects that intensify disease symptoms. Understanding the molecular dynamics during concurrent infection provides essential insight into the host response. The transcriptomic pattern of cucumber plants infected with a necrotrophic pathogen, Pythium spinosum, and a biotrophic pathogen, Cucumber green mottle mosaic virus (CGMMV) was studied at different time points, under regimes of single and co-infection. Analysis of CGMMV infection alone revealed a mild influence on host gene expression at the stem base, while the infection by P. spinosum is associated with drastic changes of gene expression. Interestingly, the comparison of P. spinosum as a single infecting pathogen with a later co-infection by CGMMV, revealed a rapid host response as early as 24 hours post-CGMMV inoculation with a sharp downregulation of genes related to the host defense mechanism against the necrotrophic pathogen. Suppression of the defense mechanism of co-infected plants was followed by severe stress, including 30% plants mortality and in increase of the P. spinosum hyphae. The first evidence of defense recovery against the necrotrophic pathogen only occurred at 13 days post viral infection. These results imply a time window in which the plants are most susceptible to P. spinosum after CGMMV infection.